Analysis of Electrocardiograms by Digital Computer - Pipberger, H. V. (Methods of Information in Medicine, 1962)
A method for automatic analysis of the P-QRS-T complex of the electrocardiogram by means of digital computers has been described. Three corrected orthogonal ECG leads (FRANK system) are recorded simultaneously on magnetic analog tape. Consequently the data are converted into digital form with a sampling rate of 1,000/sec. In this form records are fed into a digital computer. A number of analytical computer programs for ECG analysis have been developed. Application of these methods to large samples of normal and abnormal records showed that parameters of spatial direction exceeded largely those of magnitude when diagnostic recognition rates were compared. Thus, application of ECG leads which lend themselves to accurate spatial analysis appear mandatory for any improvement of electrocardiography as a diagnostic tool.Eine Methode zur automatischen Auswertung des P-QRS-T-Komplexes im Elektrokardiogramm mit Hilfe von digitalen Elektronenrechnern wird beschrieben. Drei korrigierte orthogonale EKG-Ableitungen (System FRANK) werden auf magnetischem Analog-Band simultan aufgenommen. Dann werden diese Befunde mit einer Geschwindigkeit von 1000 Imp./sec. in digitale Impulse übersetzt, in eine digitale Rechen anläge eingegeben und maschinell ausgewertet. Mehrere Analysenprogramme wurden aufgestellt. Die Anwendung dieser Methode auf eine große Zahl normaler und abnormer EKG-Befunde ergab, daß bei einem Vergleich die vektoriellen Parameter die skalaren an diagnostischer Aussagekraft bei weitem übertrafen. So erscheint die Anwendung von EKG-Ableitungen, die einer exakten räumlichen Auswertung zugänglich sind, unumgänglich für eine Verbesserung der Elektrokardiographie als eines diagnostischen Hilfsmittels.